High-order asymptotics of a solution of one problem of optimal control over a distributed system with rapidly oscillating coefficients - Kogut, P. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
High-order asymptotics is constructed and justified for optimal control over parabolic systems with rapidly oscillating coefficients in the principal part that describes high-intensity heat transfer processes in inhomogeneous and periodic media. The investigation is based on the use of methods of multiscale asymptotic decomposition and some results of the theory of averaging.